Identification of CD4_Naive cells related gene FMO4 as a positive regulator of the poor prognosis of septic CRC patients - Weiye Hou; Peiwen Fu; Zhenling Nie; Wanye Wang; Jingjing Li; Bangshun He; Qiao Tang; Tianyi Gao (Cancer Cell International)
Abstract Background Septic disease usually results in delayed access to intensive care and poor outcomes in CRC patients. Studies have shown that T cells play important roles in CRC and sepsis immune systems. Hence, this study was performed to investigate the role of T cells and T-cell-related genes in CRC-related sepsis prognosis. Methods Single-cell sequencing data from CRC and sepsis patients were first analysed to explore common T-cell signals, including those related to cellular communication and signalling pathways. Then, functional enrichment analysis and Mendelian randomization (MR) analysis were conducted on marker genes of T cells to identify the key genes and their effects on septic CRC. The expression of key genes and their associations with CRC prognosis were validated in 32 blood samples from CRC patients with sepsis. Results Compared with that in the negative control group, CD4_Naive cells infiltration was significantly lower in the combined single-cell sequencing data analysis of CRC and sepsis patients (p < 0.05). Our MR analysis and clinical sample verification results revealed that a high FMO4 gene was negatively associated with CD4_Naive cells infiltration and related to poor prognosis in septic patients with CRC (p < 0.05). The functional enrichment analysis of FMO4 revealed that FMO4 participated mainly in xenobiotic catabolic processes and taurine and hypo-Taurine metabolism in septic CRC, which further inhibited the energy metabolic activity of CD4_Naive cells. Conclusion The CD4_Naive cells related gene FMO4 appears to promote poor prognosis in septic CRC patients, suggesting that it is a promising candidate for therapeutic intervention.